Institutional and Market Pressures on Interorganizational Collaboration and Competition Among Private Human Service Organizations. Issue 1 (1st January 2017) - Bunger, Alicia C.; McBeath, Bowen; Chuang, Emmeline; Collins-Camargo, Crystal
ABSTRACT: While private human service organizations face institutional pressures to collaborate, market-based pressures also generate competition, giving rise to complex interorganizational relationships. The current study draws on institutional and resource dependence theories to examine institutional and market-based environmental pressures on the intensity of collaboration and competition among private human service organizations. Using data from the National Survey of Private Child and Family Serving Agencies, we find that the intensity of interorganizational relationships is associated with market-based and mimetic pressures but not with other institutional factors. These findings suggest practical implications for human service leaders focused on managing interorganizational collaboration and competition.